Global burden and epidemiological trends of paediatric-onset multiple sclerosis: a cross-sectional analysis of the 2021 global burden of disease study - Zhuo, Ziliang; Zhao, Zongbo; Yan, Manyun; Tan, Jianing; Gu, Yang; Zhong, Wei; Zhang, Yao; Liu, Hui (Frontiers in Pediatrics, 2025)
BackgroundPaediatric-onset Multiple Sclerosis (POMS) is a rare autoimmune disorder of the central nervous system, primarily affecting children and adolescents, characterized by recurrent episodes of neurological impairment. This study delineates the global disease burden and epidemiological characteristics of this condition.MethodsData on POMS were obtained from the 2021 Global Burden of Disease (GBD) Study, including estimates from 1990 to 2021. We described the global burden of POMS using incidence, prevalence, DALYs (Disability-Adjusted Life Years), YLDs (Years Lived with Disability), and age-standardized rates. We utilized the Joinpoint Regression Program to analyze the epidemiological trends of POMS disease burden over the past three decades. The Nordpred model was employed to project the future disease burden of POMS.ResultsIn 2021, the global incidence number of POMS was 1,899 (95% CI: 1,096–2,868), with an ASIR of 0.09 (95% CI: 0.05–0.14). The global prevalence number of POMS was 5,276 (95% CI: 2,921–7,880), with an ASPR of 0.25–95% CI: 0.14−0.38). The global DALYs for POMS was 3,073 (95% CI: 2,216–4,142), with an age-standardized DALYs rate of 0.15 (95% CI: 0.10–0.20). The global YLDs for POMS was 1,489 (95% CI: 737–2,529), with an age-standardized YLDs rate of 0.07 (95% CI: 0.03–0.12). Using Joinpoint Regression, we found that during 1990–2021, the AAPC for global ASIR was 0.07 (95% CI: 0.06–0.07), for global ASPR was 0.05 (95% CI: 0.05–0.05), for global age-standardized DALYs rate was −0.31 (95% CI: −0.34 to −0.28), and for global age-standardized YLDs rate was 0.05 (95% CI: 0.05–0.05). According to the Norpred model, by 2046, the global incidence number of POMS is projected to be 1,760 with an ASIR of 0.14. The global prevalence number of POMS is projected to be 4,915 with an ASPR of 0.38. The global DALYs number of POMS is projected to be 2,694 with an age-standardized DALYs rate of 0.21. The global YLDs number of POMS is projected to be 1,387 with an age-standardized YLDs rate of 0.11.ConclusionPOMS is characterized by a relatively low disease burden; however, it has shown a persistent upward trend in recent years. It is necessary to increase focus on this disease and develop new therapeutic approaches.